2000
DOI: 10.4049/jimmunol.165.5.2683
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lipopolysaccharide Binding Protein, CD14, and Toll-Like Receptors in the Initiation of Innate Immune Responses byTreponemaGlycolipids

Abstract: Culture supernatants from Treponema maltophilum associated with periodontitis in humans and Treponema brennaborense found in a bovine cattle disease accompanied with cachexia caused a dose-dependent TNF-α synthesis in human monocytes increasing with culture time. This activity could be reduced significantly by blocking the CD14-part of the LPS receptor using the My 4 mAb and by polymyxin B. In the murine macrophage cell line RAW 264.7, Treponema culture supernatants induced TNF-α secretion in a LPS binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 71 publications
6
122
0
2
Order By: Relevance
“…Taken together, we found that Tm-Gp, in contrast to the extracts of small-sized Treponema species [18,19], does not activate host cells but is capable of inhibiting intracellular signaling induced by LPS and PGN by blocking the function of LBP and/or CD14. In such immunomodulating active components, marginal variations of the detailed structures, such as the variations of acylation and phosphorylation patterns in the lipid A of LPS, are well-known to be closely related to their effects [43].…”
Section: Inhibitory Effect Of a Glycoconjugate On Cell Activation Andmentioning
confidence: 67%
See 4 more Smart Citations
“…Taken together, we found that Tm-Gp, in contrast to the extracts of small-sized Treponema species [18,19], does not activate host cells but is capable of inhibiting intracellular signaling induced by LPS and PGN by blocking the function of LBP and/or CD14. In such immunomodulating active components, marginal variations of the detailed structures, such as the variations of acylation and phosphorylation patterns in the lipid A of LPS, are well-known to be closely related to their effects [43].…”
Section: Inhibitory Effect Of a Glycoconjugate On Cell Activation Andmentioning
confidence: 67%
“…Glycolipids from small-sized Treponema species have been shown to exhibit activating ability upon host cells [18,19]. In contrast, Tm-Gp exhibited no activation of Mono Mac 6 cells at the highest concentration tested (100 ?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations